Substance P stimulates differentiation of mice osteoblast through up-regulating Osterix expression - 孙海飚 陈君长 刘强 郭敏锋 张华平 (Chinese journal of traumatology, 2010)
Objective： To investigate the molecular pathway of substance P （SP） to induce osteoblastic differentiation. Methods： Mesenchymal stem cells were isolated and cultured. The cultures were divided into four groups with Group A （control group） cultured without any factors, Group B cultured with SP, Group C cultured with SP and SP receptor neurokinin-1 （NK1） antagonist, and Group D cultured with SP NK1 antagonist respectively to induce osteoblastic cells differentiation. Osterix gene expression was detected by reverse transcription-polymerase chain reaction （RT-PCR） for three times after 1-2 weeks of cultivation and the results were analyzed by one-way analysis of variance （ANOVA）. Results： The log phase of bone marrow stromal cells appeared at 4-6 days. ALP staining revealed that the majority of cells, more than 95%, were positive and small bluepurple granules were found in the cytoplasm. And Group B, treated with SP, showed a higher level of ALP activity than the other three groups. Meanwhile, RT-PCR found that Osterix expression in Group B was obviously up-regulated, compared with other groups. But Osterix expression in Group D had no remarkable differences, compared with the controls. Conclusions： SP can up-regulate Osterix gene expression to stimulate differentiation of mesenchymal stem cells into osteoblastic cells at the final stage. The regulatory effect of SP on Osterix expression was dependant on SP NK1 receptors.